Analysis of lead molybdate and lead tungstate synthesized by a sonochemical method - Phuruangrat A. (2014)
Lead molybdate and lead tungstate nanoparticles were successfully synthesized by a sonochemical method for 1 h. XRD patterns showed the body-centered tetragonal structures of PbMoO4 and PbWO4, and were in accordance with those of the simulation and JCPDS software. Calculated lattice parameters are a = b = 5.4233 Å and c = 12.1253 Å for PbMoO4, and 5.4570 Å and 12.0995 Å for PbWO4. They are in accordance with those of the corresponding JCPDS software. TEM images show that the particles were 29.09 ± 5.22 nm and 21.05 ± 2.68 nm for PbMoO4 and PbWO4, respectively. Raman and FTIR vibrations were investigated to identify a definite existence of the structures. © 2009 Elsevier B.V. All rights reserved.